2013
DOI: 10.3390/molecules18078230
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Transient-State Kinetic Isotope Effects to the Resolution of Mechanisms of Enzyme-Catalyzed Reactions

Abstract: Much of our understanding of the mechanisms of enzyme-catalyzed reactions is based on steady-state kinetic studies. Experimentally, this approach depends solely on the measurement of rates of free product appearance (d[P]/dt), a mechanistically and mathematically complex entity. Despite the ambiguity of this observed parameter, the method's success is due in part to the elaborate rigorously derived algebraic theory on which it is based. Transient-state kinetics, on the other hand, despite its ability to observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Transient-state kinetics deals with very rapid reactions. The reaction mechanisms are directly related to the structure of the enzyme (Alberty 2010a ; Fisher 2013 ). Steady-state enzyme kinetics are based on the assumption that the steps in the catalytic mechanism follow steady-state kinetics, with all the state variables remaining constant, despite exposure to continuous changes (Martin 2011 ).…”
Section: Complexity Of Kinetic Mechanismsmentioning
confidence: 99%
“…Transient-state kinetics deals with very rapid reactions. The reaction mechanisms are directly related to the structure of the enzyme (Alberty 2010a ; Fisher 2013 ). Steady-state enzyme kinetics are based on the assumption that the steps in the catalytic mechanism follow steady-state kinetics, with all the state variables remaining constant, despite exposure to continuous changes (Martin 2011 ).…”
Section: Complexity Of Kinetic Mechanismsmentioning
confidence: 99%
“…In addition, the kinetics of these reactions has been published recently [29,30]. Numerous kinetic studies have been reported by the stopped-flow method [31,32]. In our previous works, the applications of the stopped-flow technique in kinetic and mechanistic studies have been reported for some organic synthesis reactions as cyclic crystalline phosphorous and pyrrole phosphorous ylides [33,34].…”
Section: Introductionmentioning
confidence: 99%